Prevalence of Dental Fluorosis and Concentration of Fluoride in Drinking Water at Sumbrungu in the Bolgatanga Metropolis - Edusei, Enoch (2014)
A Thesis submitted to the Department of Environmental Science,Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the degree Of Master Of Science in Environmental Science.